Association between different lipid parameters and aortic stiffness: clinical and therapeutic implication perspectives. Issue 11 (November 2019) - Vallée, Alexandre; Lelong, Hélène; Lopez-Sublet, Marilucy; Topouchian, Jirar; Safar, Michel E.; Blacher, Jacques
Abstract : Introduction: Recommendations about lipid parameters varied from different guidelines. Aortic stiffness is a marker of vascular aging and may reflect occurrence of cardiovascular diseases. Aortic pulse wave velocity (PWV), a marker of aortic stiffness, can be measured by applanation tonometry. The purpose of our study was to test the associations between lipid parameters and aortic stiffness. Methods: A cross-sectional study was conducted from 2012 to 2017, 603 participants were included: 517 patients and 86 'healthy' individuals used to calculate the theoretical PWV. Lipid parameters, including total cholesterol, triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL), non-HDL, total cholesterol/HDL ratio, triglycerides/HDL ratio and LDL/HDL ratio were measured. Theoretical PWV can be calculated according to age, sex, mean blood pressure and heart rate, allowing to form an individual PWV index [(measured PWV − theoretical PWV)/theoretical PWV]. PWV index [(measured PWV − theoretical PWV)/theoretical PWV] greater than 0 defined aortic stiffness. Results: In multiple linear regression analyses, total cholesterol ( P = 0.03), LDL ( P = 0.04), non-HDL ( P = 0.03), total cholesterol/HDL ( P = 0.01) and LDL/HDL ( P = 0.03) were significantly correlated with PWV. In multiple logistic regression analyses, non-HDL [OR = 1.12 (1.04–1.20), P = 0.01, R value: 0.224], total cholesterol/HDL [OR = 1.12 (1.02–1.22), P = 0.03, R value: 0.219] and total cholesterol [OR = 1.11 (1.01–1.23), P = 0.03, R value: 0.209] were significantly associated with aortic stiffness. Conclusion: Non-HDL, total cholesterol and total cholesterol/HDL were significantly associated with aortic stiffness than others and especially individually lipid parameters. This result should be considered in future clinical lipid-lowering trials. Abstract : Supplemental Digital Content is available in the text